PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN , DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR (Studi Kasus Perusahaan Makanan dan Minuman Yang Terdaftar Di BEI Tahun 2018-2019) - Lusianna Juwita Sihombing; Erny Luxy D Purba (Universitas Negeri Medan (UNIMED), 2021)
Analysis of the company's financial performance needs to be done to measure the extent of the company's achievements from a financial perspective. The financial statements will show whether the company can survive in the next era. If a company experiences a minus in its finances, then the risk of going bankrupt will be greater and the fate of the company and its employees will be at stake. This study aims to examine how the effect of capital structure, firm size and leverage, either partially or simultaneously, on the financial performance of manufacturing companies of Food and Beverage Companies Listed on theIndonesia Stock Exchange in 2018-2019.The population in this study were 24 manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2019 period. The sampling method used is purposive sampling, with a total sample of 17 companies, for 2018-2019 so that the research data is 34. Data collection techniques by downloading financial reports from the website www.idx.co.id. Data analysis techniques used in this study using multipleregression and hypothesis testing T test and F test. The results showed that the capital structure and size of the company have an effect on the company's financial performance, leverage has no effect on the company's financial performance, and simultaneously shows that there is an influence between capital structure, company size and leverage simultaneously on the company's financial performance.